Sliding speed influence on the tribo-corrosion behaviour of Ti6Al4V alloy in simulated body fluid. (August 2021) - Namus, Righdan; Nutter, John; Qi, Jiahui; Rainforth, W.M.
Abstract: Ti6Al4V is used in a wide variety of engineering applications and extensively in orthopaedics implants because of the excellent combination of the high specific strength and superior corrosion resistance. However, Ti6Al4V possesses poor tribological properties. The present work investigated the effect of reciprocating sliding speed on tribocorrosion properties of Ti6Al4V alloy under cathodic and open circuit potentials in simulated body fluid. The results showed a strong influence of the sliding speed on the microstructure of the worn surfaces and consequently on the wear rate under tested conditions. The wear rate at low sliding speeds was an order of magnitude lower compared to that at the faster sliding speed. Synergistic and antagonistic behaviour was strongly associated with the sliding speed. Graphical Abstract: ga1 Highlights: Reciprocating sliding speed has a significant influence on the tribocorrosion behaviour of Ti6Al4V alloy. At slow sliding speeds, the worn surfaces' microstructure is heavily deformed with nano-subdivision of β phase. At high sliding speed, the worn surfaces are deformed only in the outermost layer.